Argonaute Proteins: From Structure to Function in Development and Pathological Cell Fate Determination - Müller, Madlen; Fazi, Francesco; Ciaudo, Constance (Frontiers in Cell and Developmental Biology, 2020)
The highly conserved Argonaute protein family members play a central role in the regulation of gene expression networks, orchestrating the establishment and the maintenance of cell identity throughout the entire life cycle, as well as in several human disorders, including cancers. Four functional Argonaute proteins (AGO1-4), with high structure similarity, have been described in humans and mice. Interestingly, only AGO2 is robustly expressed during human and mouse early development, in contrast to the other AGOs. Consequently, AGO2 is indispensable for early development in vivo and in vitro. Here, we review the roles of Argonaute proteins during early development by focusing on the interplay between specific domains of the protein and their function. Moreover, we report recent works highlighting the importance of AGO post-translational modifications in cancer.